2021
DOI: 10.3389/fonc.2021.786015
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Endoscopic Resection and Radiofrequency Ablation for the Treatment of Esophageal Squamous Cell Neoplasia With Multiple Lugol-Voiding Lesions

Abstract: BackgroundLocal recurrence of esophageal squamous cell neoplasia (ESCN) and metachronous ESCN was associated with severe background esophageal multiple Lugol-voiding lesions (LVLs) even though the primary early ESCNs were treated with endoscopic resection (ER). The aim of this study is to explore the feasibility and effectiveness of combination treatments of ER and radiofrequency ablation (RFA) in patients with early ESCNs with synchronous multiple LVLs.MethodsA total of 329 patients with early ESCNs and synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In this study, LVLs were also identified as a risk factor for developing MESCC after EC removal because LVLs are essential markers for predicting the early reoccurrence of EC in the residual mucosa after ER. Previous studies have shown that patients with LVLs ( 5 , 10 , 19 , 35 , 36 ) or other types of cancers in the past ( 21 , 24 ) are prone to reoccurring EC and MESCC after removal of EC, respectively. In the qualitative analysis of factors, LVLs were identified as “definite factors,” history of multiple other cancer as a “likely factor,” while smoking, gender, age, alcohol consumption, and alcohol consumption after ER as “unclear factors” and the others as “not a risk factor.”.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, LVLs were also identified as a risk factor for developing MESCC after EC removal because LVLs are essential markers for predicting the early reoccurrence of EC in the residual mucosa after ER. Previous studies have shown that patients with LVLs ( 5 , 10 , 19 , 35 , 36 ) or other types of cancers in the past ( 21 , 24 ) are prone to reoccurring EC and MESCC after removal of EC, respectively. In the qualitative analysis of factors, LVLs were identified as “definite factors,” history of multiple other cancer as a “likely factor,” while smoking, gender, age, alcohol consumption, and alcohol consumption after ER as “unclear factors” and the others as “not a risk factor.”.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation for esophageal neoplasia involves delivering 465-kHz energy waveform through a bipolar electrode array, mounted on the outside of a balloon or on an articulated platform at the distal end of an endoscope (a HALO 360 or 90 system, Barrx Medical Inc.). Chen et al 50 reported that combination of ER and radiofrequency ablation effectively eliminated multiple LVLs in the background mucosa, leading to a reduced incidence of metachronous esophageal squamous neoplasms and local recurrence after ER. These innovative approaches hold promise in improving outcomes for patients post-ER by enhancing early detection of metachronous SCCs or potentially eliminating the need for surveillance in the future through treatment of high-risk background mucosa.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A method to prevent metachronous SCC is alcohol abstinence, which significantly reduced the cumulative incidence of metachronous esophageal SCC in a prospective cohort study [73]. Another possible method is ablation using a radiofrequency ablation device [74,75], which may reduce the risk of metachronous SCC by eliminating multiple iodine-unstained areas [75]. However, further validation is required before introducing this method into our clinical practice.…”
Section: Surveillance Of Metachronous Esophageal Scc After Esdmentioning
confidence: 99%